'Their proper place': women, work and the marriage bar in independent Ireland, c. 1924–1973. (2nd January 2022) - Foley, Deirdre
ABSTRACT: Until 1973, women in the Irish civil service were legally required to retire from employment after marriage. Certain lower grades were female only, and pay grades were demarked by both marital status and gender. The marriage bar was also observed informally in teaching and in the private sector. For women who remained single, it was difficult and unusual to achieve promotion in most fields. This article explores the complex history of the civil service marriage bar in independent Ireland, and in relation to marriage bars in teaching and certain spheres of private employment. It argues that the Catholic social concept of a 'family wage' was central to the prevalence of the marriage bar in twentieth-century Ireland. A single-income household was seen as the ideal, with female workers often viewed by a patriarchal government and religious hierarchy as a threat to male breadwinners. While protest and opposition to the marriage bar was not always widespread, the 'family wage' model of employment, although idealized from Irish independence, did not fit with economic reality and the lived experience of many women. Finally, this article highlights female activism associated with the marriage bar, its eventual abrogation, and its problematic legacy for women in Ireland.